2012
DOI: 10.1590/s1415-43662012000200006
|View full text |Cite
|
Sign up to set email alerts
|

Produção de girassol ornamental com uso de águas salobras em sistema hidropônico NFT

Abstract: Plantas de girassol ornamental 'Sol Vermelho' foram cultivadas em hidroponia com o objetivo de avaliar o uso de águas salobras sobre seu rendimento e qualidade da inflorescência. As águas salobras foram usadas para preparar a solução nutritiva e repor as perdas por evapotranspiração. O experimento foi conduzido em delineamento inteiramente aleatorizado com cinco níveis de salinidade da água: 1,51; 2,56; 3,86 e 6,19 dS m-1, obtidos pela adição de NaCl na água doce local (0,47 dS m-1) que também foi usada como t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
4
14
0
12
Order By: Relevance
“…According to Furlani (1999), pH values from 4.5 to 7.5 do not affect plant development in hydroponic systems. The pH values of the nutrient solution observed in this study agree with those found by Maciel et al (2012), who studied ornamental sunflower production in NFT hydroponic system under different salinity levels.…”
Section: Resultssupporting
confidence: 90%
“…According to Furlani (1999), pH values from 4.5 to 7.5 do not affect plant development in hydroponic systems. The pH values of the nutrient solution observed in this study agree with those found by Maciel et al (2012), who studied ornamental sunflower production in NFT hydroponic system under different salinity levels.…”
Section: Resultssupporting
confidence: 90%
“…The pH of the nutrient solution in Experiment I (Figure 2A) and Experiment II ( Figure 2B) remained in a range in which most of the nutrients are adequately available to plants, since the pH ranging from 5.5 to 6.5 does not influence negatively most cultures (MACIEL et al 2012). According to Furlani et al (1999), pH ranging from 4.5 to 7.5 does not compromise the plant growth in hydroponic systems, however, under acidic condition (below 4.0) may compromise the integrity of the cell membrane.…”
Section: Resultads and Discussionmentioning
confidence: 99%
“…In turn, ornamental sunflower crops of 'Moonbright' and 'Sunbeam' tolerate water with up to 10.9 dS m -1 conductivity (Grieve & Poss, 2010). Furthermore, Maciel et al (2012) observed the same commercial value for stems of 'Red Sun' sunflower grown in hydroponic solution up to 16.36 dS m -1 . This fact led to the idea of carrying out field tests with the use of brackish water in the production of cut flowers.…”
Section: Introductionmentioning
confidence: 75%
“…These effects on plant performance may have been due to the accumulation of salts in the soil profile, especially exchangeable sodium. However, an occasional reduction of shoot growth and biomass production does not necessarily imply a loss of commercial value of sunflower stems (Maciel et al, 2012;Oliveira et al, 2014). The strong growth of shoots is undesirable for ornamental plants, and there is a preference for ornamental sunflowers with small heads measuring less than 15 cm of diameter (Carrillo-Ávila et al, 2015).…”
Section: Resultsmentioning
confidence: 99%